Agaricus flocculosipes sp. nov., a new potentially cultivatable species from the palaeotropics - Rui-Lin Zhao; Kevin D. Hyde; Samantha C. Karunarathna; Kevin D. Hyde; Dennis E. Desjardin; Olivier Rasp; Kasem Soytong; Jacques Guinberteau; Philippe Callac (My University, 2012)
Agaricus flocculosipes is described as new from northern Thailand and Mayotte based on morphology and ITS sequence analysis. The new species is compared with similar taxa, and a comprehensive description, line drawings, and colored photographs are provided. Agaricus flocculosipes is distinguished among the species in section Arvenses by its relatively large sporocarps (110-80 mm in diameter), erect floccose squamules on the surface of the stipe, and relatively small basidiospores (less than 6.5 lm long). Phylogenetic analyses based on ITS sequence data using maximum likelihood, parsimony, and Bayesian analyses all support A. flocculosipes as being a distinct species within section Arvenses. The new taxon is potentially cultivatable as it is presumably heterothallic, exhibits extensive genetic diversity, and occurs in section Arvenses, a lineage that contains other edible cultivatable taxa such as Agaricus arvensis and Agaricus subrufescens.
Keywords: Heterothallic; Stipe (mycology); Agaricus; Agaricales; Maximum parsimony; Mycorrhizal Fungi and Plant Interactions